Investigation of the efficacy of generic and brand-name salmeterol/fluticasone combination in the management of asthma: a randomized comparative trial - Panahi, Yunes; Ghanei, Mostafa; Maghsoudi, Hooshyar; Saffar Soflaei, Sara; Sahebkar, Amirhossein (Acta Biomedica Atenei Parmensis, 2018)
Background: Asthma is the most chronic inflammatory disease of the airways worldwide. Combination therapy with inhaled fluticasone and salmeterol is a common practice for the long-term management of asthma. Seretide® and Fluticort plus® are two available generic and brand name products of salmeterol/fluticasone. This study aimed to compare the efficacy and safety of these two drugs. Materials and Methods: In this randomized comparative, clinical trial, 80 asthmatic patients were allocated to Fluticort plus® (n=40) or Seretide® (n=40) for a period of 4 weeks. Patients with mild asthma were instructed to inhale one puff each 12 hours and those with moderate asthma two puffs every 12 hours. Respiratory volumes (assessed using spirometry), quality of life (assessed using St. George’s Respiratory Questionnaire [SGRQ]) and control of asthmatic symptoms (assessed using asthma control test [ACT]) were evaluated at baseline and at the end of the study. Results: ACT score improved only in the Fluticort plus® group (p=0.012) while it was not significantly changed in the Seretide® group (p=0.178). In both treatment groups, FEV1, FEV1/FVC, and total as well as subscale SGRQ scores were significantly improved by the end of the study (p